The Combination of Kersen (Muntingia calabura) and Sirsak (Annona muricataL.) Leaf Extract as an Antioxidant Against Broiler Chicken Carcasses (Talenta Publisher, 2023)
Antioxidants are molecules that can slow down or prevent the oxidation process of other molecules. This study aims to determine the effect of the combination of Kersen Leaf/KL (Muntingia calabura) and Sirsak Leaf/SL (Annona muricata L.) extracts as antioxidants on Cutting Weight, Carcass Weight and Carcass Percentage of broiler chickens. This research was conducted on Jl. Mekar Jaya No 38 Medan Selayang, North Sumatra in June - August 2023. The design used in this study was a Complete Randomized Design (CRD) with 5 treatments and 5 repeats. Each repetition consists of 5 broiler chickens aged 35 days. The treatment consisted of P0 (without extract), P1 (KL extract 9%), P2 (SL extract 9%), P3 (KL extract 6% + SL extract 3%) and P4 (KL extract 3% + SL extract 6%). The parameters observed were cutting weight, carcass weight and carcass percentage. The results showed that the use of a combination of KL and SL extracts as antioxidants had a real effect on cutting weight and carcass weight with an average of 1491.67-1773.60 g/head and 1067-1267 g/head respectively. However, it did not have a real effect on carcass percentage with an average of 71.16%-72.14%. In conclusion, application of kersen leaf 6% combine with sirsak leaf 3% extract caused thee best results on cutting weight and carcass weight